ACTIVE VOLCANOES OF KAMCHATKA: SPATIAL AND TEMPORAL DYNAMICS OF ERUPTIVE INTENSITY AND PRODUCTIVITY - Kozhemyaka N.N. (My University, 2000)
The total volumes of volcanic rocks and average annual productivities of active volcanoes were calculated for all volcanic zones of Kamchatka for the mid-Pleistocene, Late Pleistocene, and Holocene epochs. Average values were computed for heat and mass transfer. A distinct spatial trend of recent volcanism was substantiated: a growth of the intensity and productivity of volcanism in a northward direction. The temporal trend was the growth of activity in the Late Pleistocene and Holocene with a peak during the Holocene.
Keywords: Holocene; Pleistocene; Cenozoic::Quaternary::Holocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Голоцен; Кайнозой::Четвертичная::Плейстоцен